2009
DOI: 10.1017/s0033291709991310
|View full text |Cite
|
Sign up to set email alerts
|

Support for the mutual maintenance of pain and post-traumatic stress disorder symptoms

Abstract: These findings provide evidence of mutual maintenance between pain and PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
114
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 51 publications
23
114
2
Order By: Relevance
“…According to this model, persons with PTSD experience exacerbating pain because they use avoidance as a coping strategy, have reduced activity levels, and attentional biases towards perceiving stimuli as implying danger. This model has received some empirical support among injured patients (Jenewein et al, 2009; Liedl et al, 2010) and in persons exposed to childhood abuse (Raphael, Spatz, & Widom, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…According to this model, persons with PTSD experience exacerbating pain because they use avoidance as a coping strategy, have reduced activity levels, and attentional biases towards perceiving stimuli as implying danger. This model has received some empirical support among injured patients (Jenewein et al, 2009; Liedl et al, 2010) and in persons exposed to childhood abuse (Raphael, Spatz, & Widom, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Carleton et al (2009) found chronic pain comorbid with generalized anxiety disorder. Liedl et al (2010) provided evidence for the mutual maintenance of pain and symptoms of PTSD, consistent with the model of Sharp and Harvey (2001). Sharp and Harvey (2001) had argued that patients with PTSD consider their pain experience as a constant reminder of the triggering event.…”
Section: Painmentioning
confidence: 58%
“…Sharp and Harvey (2001) had argued that patients with PTSD consider their pain experience as a constant reminder of the triggering event. In this regard, Liedl et al (2010) found that baseline posttraumatic re-experiencing symptoms were related to the same symptoms at 12 months; moreover, they were mediated by levels of pain at 3 months. Another relevant model is that of Liedl and Knaevelsrud (2008).…”
Section: Painmentioning
confidence: 86%
See 1 more Smart Citation
“…The difficulty in treating polytrauma obtains because of mutual maintenance factors (e.g., Liedl et al 2010, for pain and PTSD). Vicious circles develop that exacerbate reciprocally the conditions, e.g., through hyperarousal and hypersensitization (McFarlane 2010).…”
Section: Treatmentmentioning
confidence: 99%